Price of partition : recollections and reflections - Zakaria, Rafiq, 1920- (Mumbai : Bharatiya Vidya Bhavan, 2002)
Presentation of events and circumstances leading to the partition of India.
"Published on the occasion of the fiftieth anniversary of India's independence and the martyrdom of Mahatma Gandhi."
Includes index.
Keywords: India -- History -- 1947-; India -- Politics and government -- 1919-1947.